Butter side up! : the delights of science - Pyke, Magnus (J. Murray, 1976)
Dr. Magnus Pyke, a modern day scientist, explains in simplified terms the mysteries of everyday occurrences, such as: Does a buttered slice of bread always fall butter side down?